Blue smoke - Roberts, Nora. (New York : G.P. Putnam's Sons, 2005)
Pursuing a career as an arson investigator after a fire destroys her family's pizzeria, Reena Hale embarks on a relationship with Bo Goodnight and is targeted by an arsonist who taunts her with threatening phone calls.
Keywords: Arson investigation -- Fiction; Women -- Maryland -- Fiction; Psychopaths -- Fiction; Baltimore (Md.) -- Fiction; Psychological fiction; Suspense fiction